2005
DOI: 10.1377/hlthaff.w5.199
|View full text |Cite
|
Sign up to set email alerts
|

Challenges In Improving Care For High-Risk Seniors In Medicare

Abstract: Despite strong interest in improving care for high-risk elders, demonstration projects typically show negative results. This paper examines one large foundation-sponsored initiative to gain insight on why success often is so elusive. The findings indicate that specific flaws in concept, design, and implementation each make it more challenging for demonstrations to achieve their intended goals, especially those involving cost and utilization reductions. We speculate that part of the reason for this is that orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…It is worth noting that the Mercy Program in the MCCD, in which a reduction in hospital use was realized, used a combination of telephone and in-person contact. These findings support assertions by some scholars that recent demonstration projects may have been too conservative in terms of intervention design in that it was assumed that small amounts of resources (such as telephone contact) directed at incremental change can be effective in improving chronic care (Gold, Lake, Black, & Smith, 2005). Rather, it appears that nurse in-home visit interventions in conjunction with telephone consultations rather than telephone consultations alone may be needed to achieve positive functional and costs outcomes in the target Medicare population.…”
Section: Discussionsupporting
confidence: 75%
“…It is worth noting that the Mercy Program in the MCCD, in which a reduction in hospital use was realized, used a combination of telephone and in-person contact. These findings support assertions by some scholars that recent demonstration projects may have been too conservative in terms of intervention design in that it was assumed that small amounts of resources (such as telephone contact) directed at incremental change can be effective in improving chronic care (Gold, Lake, Black, & Smith, 2005). Rather, it appears that nurse in-home visit interventions in conjunction with telephone consultations rather than telephone consultations alone may be needed to achieve positive functional and costs outcomes in the target Medicare population.…”
Section: Discussionsupporting
confidence: 75%
“…Recent federal legislation has authorized demonstrations by the Centers for Medicare and Medicaid Services (CMS) of payment and service models to improve outcomes for public beneficiaries with chronic illness. 3 On the basis of experience with similar demonstrations sponsored by foundations and government programs, Gold et al (2005) argued that relatively small amounts of resources directed at incremental change are unlikely to significantly change the outcomes and cost of care for elderly patients with complex needs.…”
mentioning
confidence: 99%
“…In some instances, even when improvement in process measures (such as exercise or physical performance) has been observed, no impact on function has been demonstrated. 20,37,38 For example, two recent reviews 39,40 of 28 randomized controlled trials regarding nurse home visiting interventions found largely favorable but statistically nonsignificant effects on functional decline.…”
Section: Discussionmentioning
confidence: 99%